Rewriting Women in Romance Through Taylor Swift’s Song - Sentana, Yuli Mahmudah (Universitas Negeri Semarang, 2024)
Romance is always referred to as a way for men to dominate women through the identity, roles and attitudes that women must carry out in a love relationship. However, in the development of feminism, the breaking of masculine and feminine stereotypes has the effect that love no longer restrains women. As a female singer and songwriter, Taylor Swift tells many romance stories in her songs. This research discusses how Swift rewrites women in romance. The twelve selected songs explain that women know their existence, identity, position, and thoughts in romantic relationships. Gender equality in romance is also expressed in these songs through how women can become subjects in romance. She has the same role, status, desires and rights as men in romance. Women cannot only choose to break up but also take responsibility and face separation as well as men. She dared to separate, did not whine, and could continue life without her lover.